Bile Diversion Improves Metabolic Phenotype Dependent on Farnesoid X Receptor (FXR). Issue 5 (1st April 2019) - Pierre, Joseph F.; Li, Yuxin; Gomes, Charles K.; Rao, Prahlad; Chang, Eugene B.; Yin, Deng Ping
Abstract : Objective: The current study investigated whether bile diversion (BD) improves metabolic phenotype under farnesoid X receptor (FXR) deficiency. Methods: BD was performed in high‐fat diet (HFD)‐fed FXR knockout (FXRko) and wild‐type (WT) animals. Metabolic phenotypes, circulating enteroendocrine hormones, total bile acids (BAs) and BA composition, and cecal gut microbiota were analyzed. Results: FXR‐deficient mice were resistant to HFD‐induced obesity; however, FXR‐deficient mice also developed hyperglycemia and exhibited increased liver weight, liver steatosis, and circulating triglycerides. BD increased circulating total BAs and taurine‐b‐muricholic acid, which were in line with normalized hyperglycemia and improved glucose tolerance in HFD‐fed WT mice. FXR deficiency also increased total BAs and taurine‐b‐muricholic acid, but these animals remained hyperglycemic. While BD improved metabolic phenotype in HFD‐fed FXRko mice, these improvements were not as effective as in WT mice. BD increased liver expression of fibroblast growth factor 21 and peroxisome proliferator‐activated receptor γ coactivator‐1β and elevated circulating glucagon‐like peptide‐1 levels in WT mice but not in FXRko mice. FXR deficiency altered gut microbiota composition with a specific increase in phylum Proteobacteria that may act as a possible microbial signature of some diseases. These cellular and molecular changes in FXRko mice may contribute to resistance toward improved metabolism. Conclusions: FXR signaling plays a pivotal role in improved metabolic phenotype following BD surgery.